Lawrie's meat science. - Toldra, Fidel; Lawrie, R. A. (Ralston Andrew) (Woodhead Publishing in food science, technology, and nutrition., 2022)
Lawries' Meat Science, Ninth Edition continues to be a classic reference in the meat world. It has been used by numerous generations of meat professionals since its first edition in 1966. The new edition brings four new chapters and updated information related to the latest advances in meat animals breeding and technologies for meat preservation, processing, and packaging. In addition, new relevant aspects of nutritional value, quality and safety of meat as well as methodologies for authenticity and traceability are provided with a compilation of chapters written by a select group of the most experienced and knowledgeable people in the meat field. This book covers essential information and latest advances and developments, from the initial meat animal's growth and development to the time of slaughter and to the processing technologies, packaging and distribution till consumption of its meat. Relevant aspects of its composition, nutritional value, eating quality, consumer acceptance, safety and sustainability issues are also covered.